Repetition in German advertisement is a speech act, contributing to the realization of the advertiser's strategy - A N Mamedov (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2011)
We suppose that syntactic units in similar positions affecting the subconscious of the prospective customer can transform into emotional images according to the indirect strategy of the advertiser's manipulating influence.